(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The discovery of social dialect is an important step in the way of understanding the specificity. The youthspeak appears from the needs of certain of its bearers and is psychologically conditioned. In spite of a large number of works on the study of youth slang speech, the questions of its history are still not resolved. The article presents the results of a diachronic approach to the description of Russian’s youth jargon. On the memorial of art, journalistic, historical and scientific material the functions are revealed: communicative, integrative, adaptive, conspiratorial, actable, emotional expressive, nominative, worldview, etc. The results of the research showed that the functions of the youth social dialect are diverse and interdependent, their number is increasing or decreasing with time, the hierarchy changes.